Separated adsorption and bacterial degradation of microcystins in GAC filtration. (8th June 2009) - Wang, Haixiang; Lewis, David; Newcombe, Gayle; Brookes, Justin; , Lionel Ho
For removal of microcystins from drinking water, Granular Activated Carbon (GAC) filtration has shown to be promising as it is not only an efficient adsorbent, but also can support biodegradation of microcystins, extending the lifetime of this application. In this study, a sterile and non-sterile GAC column, in addition to a sand column, was studied to distinguish the adsorption and biodegradation removal mechanisms. Effective microcystin adsorption was considerably short in a virgin GAC bed, ∼10-15 days. Biodegradation was shown to be the primary removal mechanism after its commencement (∼1 month), with complete reduction until the study's completion (∼11 months).